Exploring bank account information of nominees and scammers in Thailand - Sirawongphatsara, Patsita; Pornpongtechavanich, Phisit; Sriamorntrakul, Pakkasit; Daengsi, Therdpong (Institute of Advanced Engineering and Science, 2024)
In today's digital era, people heavily depend on the internet for various tasks, such as online banking and e-commerce. While online transactions offer convenience, they also expose vulnerable individuals to potential exploitation by online scammers. The analysis and inquiry presented herein rely on data sourced from ChaladOhn, a system developed by academics and law enforcement, covering the period from February 2022 to January 2023. The comprehensive investigation reveals that each case resulted in losses under 10 million Thai Baht, accumulating to a staggering 3,100 million in damages. Notably, the fraudulent activities were traced back to the top two banks in the Thai market, referred to as the first and second bank. These banks were found responsible for; i) 28.2% and 16.0% of all scam accounts, ii) 25.6% and 20.5% of all transactions, and iii) 35.7% and 14.9% of all victim losses, respectively. The results of the inquiry must be shared with appropriate organizations and regulators due to the predicted worsening of this situation. This proactive approach aims to facilitate the development, recommendation, and implementation of effective strategies to address the escalating threat of online scams.